Lean Big Data Integration in Systems Biology and Systems Pharmacology - Ma’ayan, Avi (2014)
Datasets from recent large-scale projects can be integrated into one unified puzzle that can provide new insights into how drugs and genetic perturbations applied to human cells are linked to whole organism phenotypes. Data that report how drugs affect the phenotype of human cell-lines, and how drugs induce changes in gene and protein expression in human cell-lines, can be combined with knowledge about human disease, side effects induced by drugs, and mouse phenotypes. Such data integration effort can be achieved through the conversion of data from the various resources into single-node-type networks, gene-set libraries, or multi-partite graphs. This approach can lead us to the identification of more relationships between genes, drugs and phenotypes, as well as benchmark computational and experimental methods. Overall this lean “Big Data” integration strategy will bring us closer toward the goal of realizing personalized medicine.